Population Monitoring of Javan Leopard and Javan Gibbon in Potential Areas in Mount Halimun Salak National Park - Trisna Rizky Martiyani Ina; Dede Aulia Rahman; Yudi Setiawan; Satria Giri (Department of Forest Resources Conservation and Ecotourism - IPB University, 2022)
Mount Halimun Salak National Park (MHSNP) is one of tropical forest area in West Java which has the potential for a high diversity of flora and fauna species. One of them is an important habitat for the Javan leopard and Javan gibbon. This study aims to analyze the population density of the Javan leopard and Javan gibbon. Based on the result of this study information on the population condition of the Javan leopard and Javan gibbon in MHSNP. The data collection was conducted in February – April 2021 in Cikaniki area, Citalahab, corridor, and MHSNP Star Energy by installing camera traps and line transect method. The results of the camera trap installation could detected 12 types of mammals and 5 species of birds. There are four Javan leopard identified in this study with a sex ratio of 3 males and 1 famale (3:1) and only had one age class (adult). The estimated density of the Javan leopard by SECR is 11,19 ind/100km2. There were at least 11 javan leopards in an area 100 km2. The population density of javan gibbon in Cikaniki is 26,67 ind/km2, Citalahab is 16,67 ind/km2, and Star Energy is 8,33 ind/km2.